Islamic-Politics Da'wah in Abdurrahman Wahid's Pluralism Concept According to Non-Muslim Minorities Perspective in Meranti Islands Regency, Riau Province, Indonesia - Ghozali, Imam; Kamiluddin; Efendi, Nursal (Fakultas Dakwah UIN Saizu Purwokerto, 2023)
In the ethnically diverse nation of Indonesia, conflicts rooted in issues of Ethnicity, Religion, Race, and Inter-Group (SARA) have long been a persistent problem, particularly affecting ethnic Chinese who have faced marginalization and sociocultural challenges, including name changes and stereotypes. The Meranti Islands have been in the spotlight of the national media several times because of the various conflicts that occurred, both political conflicts and conflicts between ethnicities, tribes and even religions such as the burning of Chinese Ethnic Shophouses. These conflicts, driven by differences in interests and interference among groups, have sometimes led to tensions, discrimination, and even riots. The research aims to analyze Abdurrahman Wahid's political da'wah from the perspective of non-Muslim minority groups in the Meranti Islands Regency. This research is field research type. The research method uses qualitative methods. Data was collected through questionnaires and interviews and strengthened by a literature review. The research results show two thoughts regarding Islamic politics; first, 85% of the non-Muslim community in Meranty Island strongly supports Abdurrahman Wahid's Islamic political da'wah to be realized in public policies. The non-Muslim minority groups support Abdurrahman Wahid's political da'wah to maintain the Islamic taught about the rights and obligations of citizens and protect minority groups. With a percentage of 93%, they considered Abdurrahman Wahid to have carried out the function of Islamic teachings to do good deeds in a moderate and tolerant humanitarian and political life.